The Relationship between Routine ANC Follow-Up Program in the Final Trimester (≥36 Weeks) and Delivery Realization at Hospital X,West Java, Indonesia - Purba, Krissi Susana; Nababan, Riska Marcelina (Sekolah Tinggi Ilmu Kesehatan Sumber Waras, 2026)
Background: Structured follow-up during the third trimester is believed to influence maternal choice of delivery facility, but empirical evidence remains limited. Objective: To analyze the relationship between third-trimester ANC follow-up (≥36 weeks gestation) and institutional delivery at Hospital X, West Java. Methods: A pre-experimental study with a one-group posttest-only design was conducted on 79 pregnant women with ≥36 weeks of gestation who attended outpatient ANC between April and June 2025. Data were analyzed using Chi-Square and Fisher’s Exact Test. Results: A total of 81% of participants delivered at Hospital X. Statistical analysis showed no significant association between ANC visit frequency (p = 0.365), nurse follow-up frequency (p = 0.365), or ANC follow-up intensity (p = 0.394) and place of delivery. However, there was a proportional tendency for women with higher visit and follow-up frequencies to deliver at the same facility where they received ANC. Conclusion: Although statistically insignificant, routine ANC follow-up during late pregnancy may strengthen institutional attachment and continuity of maternal care. This strategy should be considered in ANC program development to support institutional delivery utilization.